Star trek and sacred ground : explorations of Star trek, religion, and American culture - Porter, Jennifer E., 1964-; McLaren, Darcee L., 1965- (State University of New York Press, 1999)
"Drawing on a number of methodologies and disciplinary perspectives, this book boldly goes where none has gone before by focusing on the interplay between Star Trek, religion, and American culture as revealed in the four different Trek television series, and the major motion pictures as well. Explored from a Trek perspective are the portrayal and treatment of religion; the religious and mythic elements; the ritual aspects of the fan following; and the relationship between religion and other issues of contemporary concern."--Jacket